Predictive Diagnosis of Agricultural Periurban Areas Based on Territorial Indicators: Comparative Landscape Trends of the So-Called “Orchard of Europe” - Salvador García-Ayllón (Sustainability, 2018)
The Mediterranean southeastern area of Spain has traditionally been known as the “Orchard of Europe”. This configuration, which is based fundamentally on traditional agriculture in periurban areas, has evolved in recent decades as a consequence of the sophistication of the agrifood processes transforming its landscape. In addition, tourism, the growth of cities, and the impact of the real estate bubble between 1995 and 2007 have configured important alterations which have generated heterogeneous phenomena in these periurban areas. The present article studies this process by analyzing the evolution of the territory and diagnosing its transformation at a large scale. The evolution of three very representative periurban and similar in size environments of this so-called Europe’s orchard will be compared by using different GIS tools: the El Ejido area, the Campo de Cartagena—Mar Menor area and the Huerta de Murcia area. Through the implementation of different territorial indicators, the current issues will be established from an objective and quantifiable perspective. Moreover, possible future scenarios for 2030 will be raised according to the current transformation trends. This approach will lead us to consider the concept of life cycle in the transformation process of a territory.